2021
DOI: 10.1002/pmrj.12702
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dual‐task testing on the balance and gait of people with lower limb amputations: A systematic review

Abstract: Objective: To systematically review the literature on the effect of dual-task testing on the balance and gait of people with lower limb amputations (PLLA). Literature Survey: Databases MEDLINE, EMBASE, CINAHL, PsycINFO, Web of Science, and Scopus were searched in duplicate (inception to December 1, 2020). Methodology: Inclusion criteria: participants were adults with transtibial, kneedisarticulation, transfemoral, or bilateral lower limb amputations; balance or gait was paired with a secondary task; and studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…A conceivable approach to account for the brain’s influence is through dual tasks, conditional on adequate familiarisation [ 95 ]. Dual tasks involve the concurrent performance of two tasks and are regarded as a measurement of cognitive-motor capacity as they require executive function and attentional demand [ 95 ]. Their performance usually results in decreased mobility and deteriorated gait patterns leading to increment falls [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conceivable approach to account for the brain’s influence is through dual tasks, conditional on adequate familiarisation [ 95 ]. Dual tasks involve the concurrent performance of two tasks and are regarded as a measurement of cognitive-motor capacity as they require executive function and attentional demand [ 95 ]. Their performance usually results in decreased mobility and deteriorated gait patterns leading to increment falls [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of familiarization time to habituate to the new prosthetic device may have influenced these results. As discussed earlier, the negative implications of performing dual-tasks are attributable to cognitive demands associated with prosthetic use, balance and gait disturbances, and brain adaptations [ 9 , 10 , 27 , 95 ]. Combined with the fact that dual-tasks represent daily activities, the recommendation is to include dual-task paradigms in the evaluation process of prostheses [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that PLLA perform worse on gait pace, rhythm, and variability domains during walking tasks that require dual tasking. 53 Ambulating in daily life often requires the need to perform such dual-task scenarios while walking, placing increased demands on the cognitive resources available, and subsequently decreasing gait performance. 53 The addition of dual-task training to a multicomponent exercise program may, therefore, provide benefits to coordination ability during gait required for daily life, 54 which may assist in reducing gait asymmetries.…”
Section: Discussionmentioning
confidence: 99%
“…53 Ambulating in daily life often requires the need to perform such dual-task scenarios while walking, placing increased demands on the cognitive resources available, and subsequently decreasing gait performance. 53 The addition of dual-task training to a multicomponent exercise program may, therefore, provide benefits to coordination ability during gait required for daily life, 54 which may assist in reducing gait asymmetries. In addition, advances in technology have allowed for the introduction of interventions such as VR training.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the importance of developing methods allows for objectifying the choice of the optimal level of amputation with the aim of maximally reducing this level without increasing the risk of early purulent-necrotic postoperative complications is understood [3,4]. These complications are the result of excessively «economical» amputation, when the line of excision of the limb falls on tissues with impaired tissue metabolism and insufficient oxygenation, therefore, it is important to develop diagnostic methods which would help determine the «ideal» level of amputation [5,6].…”
Section: Introductionmentioning
confidence: 99%